A New sp2‐sp2 Dialkylethylene‐Bridged Heptacyclic Ladder‐Type Arene for High Efficiency Polymer Solar Cells. Issue 4 (22nd February 2013) - Wu, Jhong‐Sian; Lai, Yu‐Ying; Cheng, Yen‐Ju; Chang, Chih‐Yu; Wang, Chien‐Lung; Hsu, Chain‐Shu
Abstract A new dithienobenzo‐carbazole (DTBC) heptacyclic arene using sp2‐sp2 dialkylethylene moiety as the bridge was successfully synthesized by Suzuki‐Miyaura cross‐coupling reaction. This facile benzoannulation planarizes the conjugated framework with the concomitant introduction of four octyl substituents, making the newly designed copolymer PDTBCDTBT exhibit solution processability, superior absorption ability, lower‐lying HOMO energy level, and crystalline nature. The solar cell using PDTBCDTBT has produced a high efficiency of 6.2%, which outperforms the corresponding sp3‐hybridized C‐bridged, Si‐bridged and N‐bridged analogous polymers.